Sosialisasi Sertifikasi Halal Sebagai Edukasi Bagi Pelaku UMKM di Kecamatan Martapura Barat - Faradilla Iedliany; Fitriyanti Fitriyanti; Nurbidayah Nurbidayah; Depy Oktavian Akbar; Gusti Khairunnisa (I-Com: Indonesian Community Journal, 2025)
Micro, Small and Medium Enterprises (MSMEs) participate in Indonesia's economic conditions, but most MSME actors still do not add halal labels to their production. This is due to the lack of literacy about halal certification. This Community Service activity aims to educate and socialize the process and benefits of halal certification for MSME actors in Sungai Rangas Village and Banteng Ulu Mobile Village, West Martapura District, Banjar Regency. The method of this activity is first, the delivery of socialization materials, video tutorial playbacks, discussion and question and answer sessions, and filling out satisfaction survey questionnaires. The results of the activity showed that 80% of participants felt very satisfied and 20% were quite satisfied with the implementation of socialization activities. This shows that activities have a positive impact in providing insight into the importance of halal certification and as a strategy in developing a sustainable business.